FaceScan: Unmasking Identity Beyond the Surface - Gupta, Atul A.; Bhavsar, Khushbu; Tekwani, Dhrashti C.; Jenna, Deepak; Soni, Kanishka; Vaghela, Rajdipsinh (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2023)
Biometrics, focusing on human behavior and features, encompasses face recognition as a vital technique. This paper offers a survey of face recognition methods, analyzing algorithms and approaches. Face recognition, crucial for security, is explored, emphasizing its computer-based recognition mechanisms. The paper provides an overview of face recognition methodology, recent techniques, and their efficacy under various conditions. Investigating potential biases in current deep learning systems, particularly towards children, reveals performance disparities. Strategies to mitigate this bias are evaluated, identifying effective fusion techniques. Recent advancements in face recognition, fueled by technological progress, have made automated systems practical and widely applicable. This review assesses the strengths, weaknesses, and current/future applications of face recognition technology, including IBM's system and its domains of application.
Keywords: Biometrics; Face Recognition; Algorithms; Methodologies; Security; Computer-Based Recognition; Deep Learning; Performance Bias; Children; Fusion Techniques; Technological Advancements; Automated Systems; Applications